Consultation dynamics and strategies: The Brighton guide. Issue 7 (July 2022) - Cooper, Maxwell; Sornalingam, Sangeetha; Heath, Jason; Fernandes, Carl; Jegatheesan, Menaka
The Brighton guide considers practical strategies that constitute 'tricks of the trade' for GP consultations. These are brought together within a framework of therapeutic history, therapeutic examination, clinical decision tools (where appropriate), and stepwise management that starts with 'low level' self-help advice. The management approach differs for mild-to-moderate and severe cases. The strategic principles have diverse origins in postgraduate GP training, medical education theory and the grey literature. They do not relate to specific clinical presentations but, instead, convey a 'tactical' understanding of the consultation. This approach takes account of the potential for divergence, even conflict, between the agendas of doctors and their patients. The Brighton guide embraces the everyday challenges faced by GPs in their consultations, including the achievement of safe management plans within the typical 10-minute encounter with relationships intact. This means conducting consultations that maintain boundaries, safe practice and punctuality while preserving time and energy for the next patient.